Digest: Ancestry mosaics hint at selection and may provide an alternative to differentiation scans. (1st August 2018) - Becher, Hannes
Abstract: We now have a flood of genomic sequencing data available to study reproductive isolation and selection in action, but how are these data best analyzed? Usually, genetic differentiation is compared between two groups, scanning along genomes. This approach has several drawbacks, and has been criticized repeatedly. An alternative, truly genetic approach, based on blocks of common ancestry in a hybrid zone setting, is presented by Hvala et al. (2018) in this issue.